Ross River virus infection surveillance in the Greater Perth Metropolitan area – has there been an increase in cases in the winter months? - Selvey, Linda A; Donnelly, Jenny A; Lindsay, Michael D; Pottumarthy Boddu, Sudha; D'Abrera, Victoria C; Smith, David W (Communicable Diseases Intelligence, 2014)
An increase in off-season (June to September) Ross River virus (RRV) notifications from the greater Perth metropolitan area was observed from 2006 to 2009. We investigated the increase to determine whether it is likely to have reflected a true increase in off-season cases. A single positive RRV IgM test result is sufficient for RRV notification but where follow-up testing was performed, the positive predictive value of an IgM test where IgG was negative was very low in the off-season and also in the season when using the only commercially available test kit. The increase in off-season notifications was not associated with an increase in off-season testing. Some Perth laboratories use more stringent notification criteria than the nationally agreed RRV case definition, and the geographical distribution of samples tested varies between laboratories. Our findings make a strong case to change the nationally agreed case definition for RRV to not accept a single IgM positive test result as laboratory definitive evidence where the IgG is negative. Our study also identified a range of challenges in interpreting changes in seasonal patterns and geographical distribution of RRV. Any such observed changes should be investigated through further data analysis and/or mosquito trapping and testing in order to assess validity. Commun Dis Intell 2014;38(2):E115–E122.